Hilfsmittel und Verfahren für zellbasiertes high content imaging - Gilbert, Daniel; Friedrich, Oliver; Lesko, Christian; Hartmann, Kristin (BioSpektrum, 2021)
Cell-based high content imaging has become a versatile and powerful method for studying e. g. cellular viability, morphology or physiology. However, high content imaging and its various applications require complex as well as expensive hardware and consumables, limiting its utility and usability. To broaden the applicability of cell-based high content imaging, we have developed tools and assaying techniques being exemplary portrayed in this article.
CRIS-Team Scopus Importer:2021-04-02

MyoBio: An automated bioreactor system technology for standardized perfusion-decellularization of whole skeletal muscle - Ritter, Paul; Cai, Aijia; Reischl, Barbara; Fiedler, Maren; Prölß, Gerhard; Frie, Benjamin; Kretzschmar, Elke; Michael, Mena; Hartmann, Kristin; Lesko, Christian; Salti, Hatiham; Arkudas, Andreas; et al. (IEEE transactions on bio-medical engineering, 2022)
Objective: Decellularizing solid organs is a promising top-down process to produce acellular bio-scaffolds for 'de novo' regrowth or application as tissue 'patches' that compensate, e.g., large volumetric muscle loss in reconstructive surgery. Therefore, generating standardized acellular muscle scaffolds marks a pressing area of need. Although animal muscle decellularization protocols were established, those are mostly manually performed and lack defined bioreactor environments and metrologies to assess decellularization quality in real-time. To close this gap, we engineered an automated bioreactor system to provide chemical decellularization solutions to immersed whole rat gastrocnemius medialis muscle through perfusion of the main feeding arteries. Results: Perfusion control is adjustable according to decellularization quality feedback. This was assessed both from (i) ex situ assessment of sarcomeres/nuclei through multiphoton fluorescence and label-free Second Harmonic Generation microscopy and DNA quantification, along with (ii) in situ assessment of the samples passive mechanical elasticity. Conclusion: We find DNA and sarcomere-free constructs after 72 h of 0.1% SDS perfusion-decellularization. Furthermore, passive elasticity can be implemented as additional online decellularization quality measure, noting a threefold elasticity decrease in acellular constructs. Significance: Our MyoBio represents a novel and useful automated bioreactor environment for standardized and controlled generation of acellular whole muscle scaffolds as a valuable source for regenerative medicine.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Biological systems; Biomechatronics; bioreactors; Biotechnology; decellularization; Inductors; Muscles; Plastics; skeletal muscle; Surgery; Tendons; tissue engineering

New oleoyl hybrids of natural antioxidants: Synthesis and in vitro evaluation as inducers of apoptosis in colorectal cancer cells - Carullo, Gabriele; Mazzotta, Sarah; Koch, Anna Maria; Hartmann, Kristin; Friedrich, Oliver; Gilbert, Daniel; Vega-Holm, Margarita; Schneider-Stock, Regine; Aiello, Francesca (Antioxidants, 2020)
Nowadays, the beneficial role of a healthy lifestyle, particularly emphasizing the quality of foods and cancer management, is accepted worldwide. Polyphenols and oleic acid play a key role in this context, but are still scarcely used as anti-cancer agents due to their bio-accessibility limits. Therefore, we aimed to synthesize a set of new oleoyl-hybrids of quercetin, morin, pinocembrin, and catechin to overcome the low bioavailability of polyphenols, throughout a bio-catalytic approach using pancreatic porcine lipase as a catalyst. The in vitro assays, using a wide panel of human cancer cell lines showed, mainly for two novel regioisomer oleoyl-hybrids of quercetin, a remarkable increase in apoptotic cell populations. We suggested that the DNA damage shown as GH2AX signals might be the major cause of apoptotic cell death. Finally, we demonstrated convincing data about two novel polyphenol-based hybrids displaying a highly selective anti-cancer cytotoxicity and being superior compared to their reference/parental compounds.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Apoptosis; Colorectal cancer; Cytotoxicity; DNA damage; HCT-116; Oleic acid; Pancreatic porcine lipase; Polyphenol hybrids; Quercetin